2022
DOI: 10.1186/s12889-022-13877-4
|View full text |Cite
|
Sign up to set email alerts
|

The economic burden of treating uncomplicated hypertension in Sub-Saharan Africa: a systematic literature review

Abstract: Background and Objectives Hypertension is one of the leading cardiovascular risk factors with high numbers of undiagnosed and untreated patients in Sub Saharan Africa (SSA). The health systems and affected people are often overwhelmed by the social and economic burden that comes with the disease. However, the research on the economic burden and consequences of hypertension treatment remains scare in SSA. The objective of our review was to compare different hypertension treatment costs across th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In a systematic review of 33 studies reporting cost of care with hypertension from sub-Saharan Africa, only 25% of the countries were represented. 105 The included studies reported costs from the public sector or used a mixed approach including private, nongovernmental, or missionary facilities. Medication costs were accountable for the most part of the monthly expenditures with a range from $1.7 to $97.1 from a patient perspective and $0.1 to $193.6 from a health care professional perspective (per patient per month).…”
Section: High Blood Pressurementioning
confidence: 99%
“…In a systematic review of 33 studies reporting cost of care with hypertension from sub-Saharan Africa, only 25% of the countries were represented. 105 The included studies reported costs from the public sector or used a mixed approach including private, nongovernmental, or missionary facilities. Medication costs were accountable for the most part of the monthly expenditures with a range from $1.7 to $97.1 from a patient perspective and $0.1 to $193.6 from a health care professional perspective (per patient per month).…”
Section: High Blood Pressurementioning
confidence: 99%
“…While the decentralization of care might address geographic barriers to hypertension care access, other factors of accessibility such as cost of care and time of services require additional and potentially different interventions. Extensively, the current and previous literature have shown that the high direct and indirect costs of care hamper patients’ use of health services and lead to poor health outcomes and among patients with hypertension, poor blood pressure control [54, 66, 90]. The time of operation of clinics, though limited evidence exists, has an impact on the staffing hence the long queues of patients at the in- and outpatient departments which discourages patients’ attendance to their appointments and encourages loss to follow-up [67, 91, 92].…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to ensure that the detachment of hypertension care from the general outpatient department or from the well-equipped hospital does not hamper the patients' initiation on hypertension treatment through the internal transfer processes and that patients with hypertension continue to receive holistic care for other health problems they might have in addition to hypertension. poor health outcomes and among patients with hypertension, poor blood pressure control [54,66,90]. The time of operation of clinics, though limited evidence exists, has an impact on the staffing hence the long queues of patients at the in-and outpatient departments which discourages patients' attendance to their appointments and encourages loss to follow-up [67,91,92].…”
Section: Discussionmentioning
confidence: 99%
“…The complications of hypertension in these countries are increasingly experienced by younger people who form the productive base of the economy. This can impede economic development and exacerbates poverty by diverting vital economic resources from other areas of national development 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…This can impede economic development and exacerbates poverty by diverting vital economic resources from other areas of national development. [5][6][7] Hypertension is frequently undetected, and untreated or suboptimally treated. 8 Each of these scenarios is associated with complications.…”
mentioning
confidence: 99%